SIFAT PAPAN SERAT DARI KAYU ACACIA MANGIUM WILLD., EUCALYPTUS DEGLUPTA BLUME DAN EUCALYPTUS UROPHYLLA BLAKE - Kayano Purba; Deden Edi Rusfiandi; Yusuf Sudo Hadi; M Rosid (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
This paper deals with the study on the fiberboard properties of A. mangium, E. deglupta and E. urophylla. The cooking process applied consisted of hot caustic soda semi chemical process and prehydrolysis prior to mechanical pulping process.The hot caustic soda semi chemical process used the condition as follows: alkali concentration was 35 g/l, wood to liquor ratio was 1 : 8, maximum temperature was 100° C and this temperature was kept for two hours. The prehydrolisis prior to mechanical process was prepared in the autoclave with the wood to liquor ratio ;of . 1 : 8, maximum temperature was 175 ± 1°C and this temperature was kept for 60 seconds, and the pressure of 7 - 12 kg/cm2. Sheet forming was done by wet felting process in the deckle box, the pressing pressure was 50 kg/cm2, temperature was 170° C for 10 mi- nutes. Heat treatment was given for 3 hours at temperature of 170° C without pressure.The result shows that the cooking process has a significant influences on the moisture content, water absorption, thickness swelling, tensile strength parallel to surface and modulus of rupture of the fiberboard. Likewise, the wood species has a significant influence on pulp yield, moisture content, water absorption and thickness swelling. The interac- tion of both factors only significantly influences modulus of rupture and modulus of elasticity.The highest pulp yield was from A. mangium followed by E. deglupta, and E. urophylla. Almost overall properties of fiberboard met the FAO standard, except for the water absorption and tensile strength parallel to surface of E. uro- phylla. The mechanical process produced fiberboard with better water absorption and thickness swelling than that of hot caustic soda semi chemical process. On the other hand the tensile strength parallel to surface and modulus of rupture of the fiberboard produced by hot caustic soda semi-chemical process was found better than that of the mechanical pulping.